Conceptual Framework of Crisis Negotiation Competency Development in Managers of Internal Affairs Bodies - Vakhnina V.V; Maidykov A.F; Ulyanina O.A (Moscow State University of Psychology and Education, 2017)
In this article the authors examine the psychological features of the development of an integral psychological concept of crisis negotiation activities from the perspective of system-situational and reflexive approaches.This research forms the basis of a new scientific direction in legal psychology, the psychology of crisis negotiation activities of employees of internal affairs bodies, as a system of coping with and preventing crisis in negotiations.The data was collected and analysed in several stages from 1995 to 2014 and included a survey of managers of internal affairs bodies as well as a systematic analysis of the data pool of 1705 crisis situations.Basing on the analysis the authors propose a matrix of negotiations which identifies priority strategies and possible crisis zones at various stages of the negotiation process depending on the characteristics of the situation, thus helping to carry out crisis negotiations effectively.